Identification of odorant-binding protein genes in Galeruca daurica (Coleoptera: Chrysomelidae) and analysis of their expression profiles. Issue 4 (20th April 2017) - Li, L.; Zhou, Y.-T.; Tan, Y.; Zhou, X.-R.; Pang, B.-P.
Abstract: Odorant-binding proteins (OBPs) play a fundamental role in insect olfaction. In recent years, Galeruca daurica (Joannis) (Coleoptera: Chrysomelidae) has become one of the most important insect pests in the Inner Mongolian grasslands of China. This pest only feeds on the species of Allium plants, implying the central role of olfaction in its search for specific host plants. However, the olfaction-related proteins have not been investigated in this beetle. In this study, we identified 29 putative OBP genes, namely GdauOBP1–29, from the transcriptome database of G. daurica assembled in our laboratory by using RNA-Seq. All 29 genes had the full-length open reading frames except GdauOBP29, encoding proteins in length from 119 to 202 amino acids with their predicted molecular weights from 12 to 22 kDa with isoelectric points from 3.88 to 8.84. Predicted signal peptides consisting of 15–22 amino acid residues were found in all except GdauOBP6, GdauOBP13 and GdauOBP29. The amino acid sequence identity between the 29 OBPs ranged 8.33–71.83%. GdauOBP1–12 belongs to the Classic OBPs, while the others belong with the Minus-C OBPs. Phylogenetic analysis indicated that GdauOBPs are the closest to CbowOBPs from Colaphellus bowringi . RT-PCR and qRT-PCR analyses showed that all GdauOBPs were expressed in adult antennae, 11 of which with significant differences in their expression levels between males and females. Most GdauOBPs were also expressed in adult heads (without antennae), thoraxes, abdomens, legs and wings. Moreover, the expression levels of the GdauOBPs varied during the different development stages of G. daurica with most GdauOBPs expressed highly in the adult antennae but scarcely in eggs and pupae. These results provide insights for further research on the molecular mechanisms of chemical communications in G. daurica .